O trabalho colaborativo entre os profissionais das políticas intersetoriais na perspectiva da formação integral das crianças da primeira infância - Santos, Sara Regina Barbosa Oliveira (2024)
This research, conducted at the Municipal School of Early Childhood Education - EMEI CEU Butantã, part of the Unified Educational Center - CEU Butantã, in the city of São Paulo, was carried out by a researcher who has been working for over six years as a school director in this educational unit, and aimed to investigate how collaborative work among professionals from intersectoral policies can contribute to the comprehensive education of young children. For this purpose, a qualitative approach was adopted, based on the concept of action research and case study strategy. Various data collection techniques were used, such as focus groups, document analysis, literature review, and participant observation. The overall objective of this study was to identify and analyze how collaborative work among professionals from intersectoral policies can contribute to the comprehensive education of young children. To achieve this goal, three specific objectives were outlined: to describe and analyze how collaborative work is carried out at EMEI CEU Butantã among professionals from education, sports, culture, and health; to identify the potentialities and challenges of collaborative work in this context; and to develop recommendations for a formative proposal that encompasses the expansion of collaborative work among these professionals. The research results revealed four main categories. Firstly, in the conception of intersectorality, there is an understanding of public policy as an essential guideline for intersectoral actions, promoting synergy and complementarity in interventions, in addition to the importance of active collaboration among the professionals involved. Secondly, in the principles that mobilize and unite professionals, the importance of open dialogue, appreciation of collective work, and commitment to common educational goals is highlighted, emphasizing the need for continuous dedication. Thirdly, in addressing challenges and proposing solutions, the management of time, space, and human resources emerges as crucial obstacles, along with the need for specific training and institutional cooperation. Finally, in the conception of comprehensive education, the importance of providing enriching experiences that go beyond the classroom, promote diverse skills, and consider the physical, emotional, and social aspects of children is emphasized, requiring integration of public services to ensure comprehensive development. When the school recognizes and shares responsibility for education with professionals from intersectoral policies, it not only strengthens its role as a protagonist but also expands its potential impact on the comprehensive education of young children. The research addressed the need to expand collaborative work among professionals from intersectoral policies for the comprehensive education of young children, focusing on the experience of EMEI CEU Butantã. The investigation, based on the researcher's immersion in the school context, contributed to the understanding of collaborative dynamics and the development of a more comprehensive and effective formative proposal